Estimating the Sound Insulation of Double Facades with Openings for Natural Ventilation. (November 2015) - Bajraktari, Egzon; Lechleitner, Josef; Mahdavi, Ardeshir
Abstract: Natural ventilation represents a potentially sustainable scheme for the provision of good indoor air quality and free cooling in buildings. However, its application is frequently hindered due to outdoor climatic conditions, air pollution, or noise pollution. The later impediment represents one of the main motivations behind the research presented in this paper, as buildings under noise exposure cannot effectively deploy the natural (window) ventilation option. To address this problem, the potential of building envelope solutions that could offer sufficient sound insulation while facilitating natural ventilation is of critical importance. Specifically, the present contribution focuses on the sound insulation properties of double facades with openings for natural ventilation. Thereby, a generic double-leaf façade was conceived and installed between two adjacent reverberant chambers in the acoustic laboratory of the Department of Building Physics and Building Ecology at the Vienna University of Technology. This experimental modular double-leaf wall allows for various configurations of open elements. Multiple opening combinations were studied, such that the impact of various system parameters (e.g., the size of the opening, location of the openings, the relative displacement of the openings in the two layers) could be assessed both empirically and computationally. Furthermore, various levels of sound absorption in the double wall cavity (realized with absorber panels) were considered and tested. The resulting comprehensive set of parametric configurations was subject of systematic sound transmission measurements. Using the results of the measurements, multivariable analysis and curve-fitting techniques were deployed toward developing empirically-based equations for the prediction of the sound insulation of double-leaf facades with openings for natural ventilation. Furthermore, a simple analytical model was proposed that could be also applied toward predicting the sound transmission of such constructions. The results of empirically-based and analytical models are compared with the measurements results to discuss the potential and limitations of their predictive performance.